2014
DOI: 10.1007/s11547-013-0359-7
|View full text |Cite
|
Sign up to set email alerts
|

Conventional 2D (2DRT) and 3D conformal radiotherapy (3DCRT) versus intensity-modulated radiotherapy (IMRT) for nasopharyngeal cancer treatment

Abstract: The findings of this study confirm that IMRT associated with chemotherapy, even with moderately hypofractionated regimens, allows good disease control with better results in terms of late xerostomia, although without statistically significant differences compared to 2DRT and 3DCRT. The hypothesis of an impact of IMRT on survival has yet to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Notably, about 70% of patients in this study were diagnosed with NPC of early stage, which matched the relative higher survival outcomes in comparison with prior reports [46, 8, 9] on the whole. When stratified by tumor stage, however, the outcomes of early stage patients treated with IMRT and 2DCRT were highly similar to the results of the studies by Su et al [14] and Zhang et al [6], respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Notably, about 70% of patients in this study were diagnosed with NPC of early stage, which matched the relative higher survival outcomes in comparison with prior reports [46, 8, 9] on the whole. When stratified by tumor stage, however, the outcomes of early stage patients treated with IMRT and 2DCRT were highly similar to the results of the studies by Su et al [14] and Zhang et al [6], respectively.…”
Section: Discussionsupporting
confidence: 87%
“…By head to head comparison, Fang et al [8] and Moretto et al [9] both found that IMRT was comparable to 2DCRT in locoregional control, DMFS and OS, despite in smaller cohorts of patients. In a phase III randomized trial [10] aiming at the efficiency of adjuvant chemotherapy in locoregionally advanced NPC, radiation technique (IMRT vs 2DCRT/3DCRT) was also not associated with any type of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 79 full articles retrieved, 38 were further excluded for no matched comparison, 19 for reviews, 12 for insufficient data, and 2 for repeated patients. Finally, 8 articles [6,[12][13][14][26][27][28][29] met the inclusion criteria and the flowchart of the retrieved studies are presented in Fig. 1.…”
Section: Search Results and Characteristics Of Studiesmentioning
confidence: 99%
“…The first part of our study (3DCRT versus IMRT) indicated that there was no significant reduction in the dose to bilateral PMCs and CSTs between the 3DCRT and IMRT plans. The critical structures adjacent to the target volume marked as OARs can be better spared during the IMRT planning process due to a steep dose gradient and a high conformity [17,18]. The second part of our study (IMRT versus IMRT_ PMC&CST), has shown that a significant reduction in the dose to bilateral PMCs and CSTs regions can be achieved without compromising the coverage of planning target volume and the limiting dose to these conventional OARs.…”
Section: Discussionmentioning
confidence: 99%